La Inversión y el Ahorro Nacional. Paradoja de Feldstein – Horioka, evidencia para Ecuador, periodo 1965 – 2017 - Pazmiño Vieira, Michelle Estefanía (2019)
In this research work headlined "Investment and National Savings. Paradox of Feldstein – Horioka, evidence for Ecuador, period 1965 - 2017", it determines the relationship between savings and investment. Each variable is analyzed in detail through statistical charts and graphs that allow to remark the behavior of each one of them in a better way during the study period. A VEC model is applied, in which there is a correlation between variables, which gives a result in a significant relationship of long term equilibrium between Savings and Investment, that means, a low capital mobility; thus, fulfilling of the Feldstein –Horioka Paradox. This research work is organized by sections: First section, Reference Framework, a brief introduction is presented, in addition to the problem of the source of the research and the setting of objectives. Second section, Theoretical Framework, the research background is developed, the theoretical foundation for each variable, an explanation about the Mobility of capitals and also a brief detail about the origin of the Feldstein- Horioka Paradox. The third section, Methodological Framework, which includes the methodology applied in the research, the analysis of national savings and investment to make known afterwards the relationship that exists between each one of the variables. Finally, in the fourth section, different conclusions and recommendations are established that were reached after the research process.